The Effect of General Allocation Funds and Special Allocation Funds on Regional Government Expenditures of Tidore Islands City Government - Abdullah Saifuddin (Peneliti.net, 2020)
This study aims to determine the effect of the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) on the regional expenditure of the City Government of Tidore Islands. This research was conducted considering that regional expenditures have been used for routine expenditures which are relatively less productive. Therefore, in an effort to improve the quality of public services, local governments should change the composition of their spending. The results of the study show that the General Allocation Fund has a positive and significant effect on the Regional Government Expenditures of the City of Tidore Kepulaun in 2016-2018. The Special Allocation Fund has a positive and insignificant effect on the realization of regional expenditure in the City Government of Tidore Islands in 2016-2018. The General Allocation Fund and the Special Allocation Fund together have a positive and significant effect on the Regional Expenditure Realization of the Tidore Islands City government in 2016-2018.